2017
DOI: 10.15406/jdmdc.2017.04.00106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Dysfunction in Diabetic Patients

Abstract: Diabetes mellitus and thyroid dysfunction are two major highly-spread health problems worldwide. Both of them affect each other, and the recognition of the relationship between diabetes mellitus and thyroid dysfunction is of importance to guide clinicians in good management of both of them. The present study aimed to find out the prevalence of thyroid dysfunction among diabetic patients in Qurayat Diabetes Center (QDC). Materials and methods:Two hundred (100 type 1 & 100 type 2) diabetic patients were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
14
2
Order By: Relevance
“…Contrary to our finding, Diez et al and Mahalingam, et al in their studies found no association [22][23]25]. The association of hyperglycemia with thyroid dysfunction may be due to the adverse effects of chronic hyperglycemia on the hypothalamic-pituitary axis where it blunts or abolishes the nocturnal TSH peak [20,14,26] . CC-BY 4.0 International license It is made available under a perpetuity.…”
Section: Glycemic Control and Thyroid Dysfunctioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our finding, Diez et al and Mahalingam, et al in their studies found no association [22][23]25]. The association of hyperglycemia with thyroid dysfunction may be due to the adverse effects of chronic hyperglycemia on the hypothalamic-pituitary axis where it blunts or abolishes the nocturnal TSH peak [20,14,26] . CC-BY 4.0 International license It is made available under a perpetuity.…”
Section: Glycemic Control and Thyroid Dysfunctioncontrasting
confidence: 99%
“…Studies have shown a very high prevalence of thyroid dysfunction in type 2 DM. Insulin and thyroid hormones are intimately involved in cellular metabolism and thus excess or deficit of either of them may result in the functional derangement of the other [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of thyroid hormone binding inhibitor (inhibitor of T 4 toT 3 conversion), can be another cause for the dysfunction in hypothalamopituitary thyroid axis and the impact of poor control of diabetes on thyroid hormone concentration. 1 T 3 level has a statistically significant with negative correlation with an increased FPG while T 4 has a non stastically significant negative correlation with increased FPG. This is because Insulin is an anabolic hormone results in inhibition of the hepatic conversion of T 4 to T 3 ,causes increases the levels of FT 4 while it decreases the levels of T 3.…”
Section: Discussionmentioning
confidence: 82%
“…The two most common endocrine disorders encountered in clinical practice all the time are Diabetes mellitus (DM) and thyroid dysfunction (TD). 1 Thyroid hormones are found to influence approximately all the metabolic pathways including carbohydrate metabolism. In contrast, in Type 2 DM, there are inconsistent and variable degrees of insulin resistance (IR) and/or impaired insulin secretion and increased glucose production.…”
Section: Introductionmentioning
confidence: 99%
“…Activity of chitotriosidase-1 elevated in patients with newly diagnosed, untreated, and uncomplicated type 2 DM which is positively linked to glucose levels, age, and asymmetric dimethylarginine (ADMA) levels of those patients .Increased ADMA levels inhibit nitric oxide production in addition to impair endothelial function [18,19].…”
Section: Resultsmentioning
confidence: 99%